Reimagining Innovation in Education and Social Sciences Proceedings of the International Joint Conference on Arts and Humanities (IJCAH 2022), September 10-11, 2022, Surabaya, Indonesia - Saroinsong, Wulan Patria; Ashar, Muhamad Nurul; Maureen, Irena Yolanita; Hartanti, Lina Purwaning; Anggaryani, Mita; Titaley, Audrey Gabriella (Taylor & Francis, 2023)
Certainly, the pandemic has affected several aspects of life. Several modifications have been made and are now continuing. The number of innovations has expanded substantially, particularly in the fields of education and social sciences. Innovations are produced by educators, scientists, and professionals. These innovations must be distributed to aid the development of society in the sphere of education and beyond. After the eradication of the disease, we shall assist one another in conquering it and then develop and prosper together. This volume contains the works of educators, researchers, practitioners, and academics presenting the most recent research results, issues, and practical difficulties and solutions found in the domains of Education, Cultural Studies, Applied Linguistics, and Community Services. Reimagining is a creative method to approach or address challenges associated with innovation in the fields of education, cultural studies, applied linguistics, community services, or social sciences. Due to the topic areas covered in this proceeding, it is appropriate for instructors, researchers, practitioners, and academics who specialize in the aforementioned subjects. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license. Funded by Universitas Negeri Surabaya, Indonesia.